PJMHS 2021
DOI: 10.53350/pjmhs211561617
|View full text |Cite
|
Sign up to set email alerts
|

Determine the Frequency of Portal Vein Thrombosis in Patients with Liver Cirrhosis

Abstract: Objective: The aim of this study is to determine the frequency of portal vein thrombosis in patients with liver cirrhosis. Study Design: Retrospective/Case-control Place and Duration: Medicine and Gastroenterology department of Peshawar Institute of Medical Sciences, Peshawar and DHQ Teaching Hospital, Charsadda for six months duration from August 2020 to January 2021. Methods: Total 100 patients of both genders were presented in this study. Patients detailed demographics age, sex and body mass index were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is speculated that the coagulation function of cirrhotic patients was generally suppressed due to hepatic failure, which is usually reflected as decreased coagulants and significantly prolonged PT, and the platelet count was decreased possibly from hypersplenism, increased immune-mediated platelet destruction and/or impaired thrombopoietin synthesis in the liver [9,20,31,32]. All of these abnormalities may prevent thrombus formation; however, this claimed auto-anticoagulation did not guarantee against PVT in cirrhotic individuals, and this confirms the complexity of the pathogenesis of cirrhosis-related PVT [26,27]. There is some evidence suggesting that antithrombotic therapy effectively induces recanalization of the thrombosed portal vein without increasing the risk of bleeding [25].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is speculated that the coagulation function of cirrhotic patients was generally suppressed due to hepatic failure, which is usually reflected as decreased coagulants and significantly prolonged PT, and the platelet count was decreased possibly from hypersplenism, increased immune-mediated platelet destruction and/or impaired thrombopoietin synthesis in the liver [9,20,31,32]. All of these abnormalities may prevent thrombus formation; however, this claimed auto-anticoagulation did not guarantee against PVT in cirrhotic individuals, and this confirms the complexity of the pathogenesis of cirrhosis-related PVT [26,27]. There is some evidence suggesting that antithrombotic therapy effectively induces recanalization of the thrombosed portal vein without increasing the risk of bleeding [25].…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have demonstrated that advanced imaging techniques have yielded 5% to 27% of patients with liver cirrhosis being diagnosed with PVT [2,9,25], and others have reported that prevalence of PVT rang-es from 0.6% to 26% in liver cirrhosis [21,22]. The prevalence of PVT in cirrhosis goes against what was previously recognized as cirrhosis-related auto-anticoagulation [26,27].…”
Section: Discussionmentioning
confidence: 98%